Pelestarian Hutan Mangrove di Dermaga Tanarajae Desa Bonto Manai, Kecamatan Labakkang, Kabupaten Pangkep - Arfandi, Arfandi; Rusdi, Rusdi; Marsanda, Suci Andriani (Indonesian Journal of Applied Geography, 2024)
The Tanarajae Pier in Bonto Manai Village, Pangkep Regency, is a coastal area with extensive mangrove forests along the shoreline. This area has become a focus for several institutions dedicated to mangrove planting activities. Mangrove forests thrive in tidal regions and offer significant ecological and economic benefits, such as carbon sequestration, coastal protection, and habitat provision for marine life. This study aims to examine the conservation efforts of mangrove forests at Tanarajae Pier, identify the types of mangroves planted, and evaluate their functions and benefits for the local community. Using a qualitative descriptive approach, data were collected through interviews with local residents and officials, as well as direct observations. The results indicate that the mangrove species present at Tanarajae Pier include Rhizophora stylosa, Sonneratia, Rhizophora apiculata, and Avicennia. These mangrove forests serve crucial roles as habitats for marine life, protect against coastal erosion, and support ecotourism initiatives, thereby enhancing community income. The most effective period for mangrove planting is between March and August, accompanied by regular monitoring to ensure optimal growth. The primary challenge in conservation is the presence of waste, which obstructs the growth of mangroves. Effective waste management strategies and increased public awareness about the importance of maintaining a clean environment and the benefits of mangroves are essential for the success of conservation efforts. This study underscores the need for integrated conservation practices to sustain and enhance the ecological and economic benefits provided by mangrove forests at Tanarajae Pier.